Financial inclusion in Ethiopia: Is it on the right track? - Tekeste Berhanu Lakew; Hossein Azadi (International Journal of Financial Studies, 2020)
It is important to evaluate the impact of Ethiopia's financial inclusion strategy since it has been launched in 2014. Accordingly, this paper assesses the extent to which the target has been met. The main aim of this study is to measure the success or failure of Ethiopia's financial inclusion in comparison with other countries in East Africa. Using secondary data, this study revealed that Ethiopia's financial inclusion is not as successful as other East African countries. This study also found that Ethiopians prefer informal saving clubs rather than formal financial organs. This preference, combined with unemployment and low income, is the barrier to the financial inclusion strategy. Based on the findings, identifying and addressing root causes should be done by removing distance, cost, credit, and documentation barriers. Moreover, the findings showed that access to public transit can also expand the reach of formal financial institutions by encouraging more people to physically access financial institutions. This study recommended access to formal financial organs as a core to financial institutions. Access to formal financial organs should be boosted through increasing financial institutions. Educating individuals about their financial circumstances were also recommended so that people can increase their formal saving uptake. This paper also recommended that the government develop regulatory guidelines for the functioning of financial institutions. Themain outcome, therefore, is that financial institutions could be more transparent and predictable, reduce costs, and simplify the rules for entering the market.
Keywords: 330; East Africa; financial exclusion; formal financial system; microfinance